DEVELOPING THE ISLAMIC MIND - Nik Roskiman Abdul Samad; Mohd Noor Omar (Khayra Ummah Series (No.2/9), 2022)
This volume is part of the Khayra Ummah series, being itself the culmination of a sequence of colloquium of several themes organised by IKIM. The issues addrressed in this series are : Islamic economics; Islamophobia; governance; moral deterioration; disruptive technology; the Islamic state and society; environmental degradation; and the Islamic mind.